SIMBOL DAN MAKNA SIRIH PINANG PADA SUKU ATONI PAH METO DI TIMOR TENGAH UTARA - Erna Suminar (Jurnal Komunikasi dan Bisnis, 2020)
This paper investigates social interaction, the meaning of messages and, human actions are activities based on certain symbols. This research focuses on the Sirih pinang tradition of the people of the Atoni Pah Meto tribe. Sirih Pinang has a role in the fundamental cultural symbols in the life of social courtesy and social interaction. Using the Symbolic Interaction Theory Herbert Blumer (1986), this study explains the symbolic function and meaning of Sirih Pinang which will be useful for everyone in establishing social, economic, educational and, political relations with the Atoni Pah Meto tribe, also for the Atoni Pah Meto community. This study uses a qualitative method with participant observation. Three Indigenous Elders who have in-depth knowledge of this tradition were critical informants in the study. Participant observations were carried out in the field by living and living with the Atoni Pah Meto tribe during the survey in the Kefetoran Aplal North Central Timor Regency, East Nusa Tenggara Province. The results of this study indicate a relationship between the Sirih Pinang symbol and the local religious beliefs of ancestral heritage. In ritual communication to honor the spirits of sirih pinang is a symbol that has ethical values ​​and meaning. Sirih Pinang is included in unifying tribal members and in breaking up as a practice of various forms of communication that has the value and meaning of family and friendship. Furthermore, humans modify the meaning, the result of developing social interaction. Sirih Pinang is used as a tool for negotiation, lobbying, and enters the realm of political communication and then experiences a shift in meaning. Keywords: Symbolic Interaction Theory, Intracultural Communication, Atoni Pah Meto Tribe, Indonesian Culture, Sirih Pinang.